The role of social capital in enhancing the performance of the local government in the Maldives - Zahir, Ahmed; Quddus, S. M. Abdul (IIUM Press, International Islamic University Malaysia, 2017)
This book investigates the relationship between social capital components, (trust, networks of civic engagement, norms of reciprocity and cooperation) with the performance of the local government of Maldives. It also sheds some light on the formation, development and the functions of the local government. In order to address the research questions, multiple methods of data collection such as interviews, questionnaires and document analysis were used. Participants and respondents for the study were selected using purposive sampling, systematic random sampling and convenience sampling. The findings suggest that there is a significant relationship between the components of social capital and local government performance, with the exception norms of reciprocity. The findings also reveal that there is a decline in the levels of citizens’ trust in the local government institutions particularly at the local levels, independent commissions and political parties. The study also indicates that the political parties influence in the local councils has stifled public participation to a high degree and there is little effort done to involve the local citizens in the decision making process.On the effects of division, institutional antagonism and lack of cooperation, the study found negative effects on the performance of the local government. The findings suggest that as a result of political competition among councillors, they are torn between fulfilling their obligations towards the local citizens and their parties. As a result, many councillors do not cooperate with the central government which is essential to provide the necessary services to the local citizens. For effective local government performance, the study suggests conducting awareness programmes for councillors to become informed about how to redirect their efforts towards improving the socio-economic well-being of their community. The implications of the study suggests that there is an urgent need to make amendments to the Local Government Act in order to reduce the unnecessary costs to administer the current local government system. The central government should be mindful to treat all councils equally. Finally, the Local Government Authority should conduct developmental programmes for the councils where they can exchange and share their ideas and experiences with other council members. In addition, more ways should be established to monitor the work of councillors on a regular basic.